Use and perception of areas of permanent preservation in an environmentally differentiated land reform settlement in Anapu, Pará: Uso e percepção de áreas de preservação permanente em assentamento ambientalmente diferenciado em Anapu, Pará - Sousa, Laís Victoria Ferreira de; Porro, Roberto (Programa de Pós-graduação em Desenvolvimento, Agricultura e Sociedade da Universidade Federal Rural do Rio de Janeiro (CPDA/UFRRJ), 2018)
This study assessed how residents of an environmentally-sound land reform settlement in Anapu, Pará, perceive and use forests and permanent preservation areas (PPAs). Quantitative methods (comparative areas from mapping) and qualitative (semi-structured interviews) evaluated the effect of tenurial situation, access to the plot and predominant economic activity in the conservation of PPAs and forests. Considering only the preservation of PPAs, the quantitative analysis showed no significant difference between groups compared. In relation to forests, greater preservation was associated with the activity carried out in the lot: prioritization of agriculture was associated with higher percentage of forests than prioritization of livestock, although no statistical relevance was observed for this association. The qualitative analysis indicated that land tenure regularity is not perceived as a factor for greater conservation of PPAs. Main differences in the use of PPA were also perceived regarding the economic activity prioritized in the lot.Keywords: environmental conservation; Amazon deforestation; agriculture; cattleranching.SOUSA, Laís Victoria Ferreira de; PORRO, Roberto.  Uso e percepção de áreas de preservação permanente em assentamento ambientalmente diferenciado em Anapu, Pará. Estudos Sociedade e Agricultura, v. 26, n. 3, p. 656-680, out. 2018.Submitted in march 2018.Accepted in august 2018.